Transformasi Pendidikan Bahasa Arab dalam Menghadapi Tantangan Global - Hidayatul Mustafidah (Al-Qalam: Jurnal Pendidikan Bahasa Arab, 2025)
The development of globalization, technological advancements, and socio-cultural dynamics demand transformation in Arabic language education to remain relevant and competitive at the global level. Arabic language education is no longer only oriented towards mastering linguistic rules, but is also required to be able to equip students with communicative competence, digital literacy, and cross-cultural understanding. This article aims to analyze the forms of transformation of Arabic language education in the face of global challenges as well as identify the factors that influence its implementation in educational institutions. This study uses a qualitative approach with a descriptive-analytical design through literature study and analysis of Arabic language learning practices. The results of the study show that the transformation of Arabic language education includes a shift in the learning paradigm from teacher-centered to learner-centered, the integration of communicative and task-based approaches, the use of digital learning technology, and the strengthening of the sociocultural dimension in learning. However, the transformation still faces various obstacles, such as the pedagogical readiness of educators, limited infrastructure, and a curriculum that is not fully adaptive to global demands. This article emphasizes the importance of developing innovative, contextual, and sustainable Arabic language education models as a strategic strategy in addressing global challenges.